Casa de Velázquez : à la recherche de la bibliothèque disparue (1920-1958) - Katie Brzustowski (Mélanges de la Casa de Velázquez)
The history of Casa de Velázquez's library is hidden behind its destruction, which has become something of a myth, and has not been the subject of any in-depth study. The sources, most of which come from the Casa de Velázquez's own archives and library, allow us to sketch out a three-stage history: firstly, before 1928, the collection of the École des Hautes Études Hispaniques, which formed the basis of the Casa de Velázquez library; secondly, the first library, which was housed in a building specifically constructed to house the Casa de Velázquez, the "Moncloa Palace", from 1928 until its destruction in 1936; and thirdly, the reconstitution of the lost library, from 1937 until its reinstallation in the rebuilt building in 1958.  The study highlights the key role played by the founders, the hallmark of the University of Bordeaux, through the figures of Pierre Paris and Yves Renouard, and, in the period of reconstitution, library practices and a living space evoked in the testimonies of readers. This initial approach opens up avenues for more detailed studies, both quantitative and qualitative. As for the original library, it will certainly retain its fair share of mystery...